SICK HEALTH BEHAVIORS OF THE JAMBI MALAY TRIBE BASED ON TRANSCULTURAL NURSING APPROACH (SUNRISE MODEL) AT MUARA KUMPEH VILLAGE KUMPEH ULU DISTRICT MUARO JAMBI REGENCY - Mila Triana Sari; Selvy Prastianty (Universitas Batanghari Jambi, 2017)
Health behaviors are actions that individuals do to improve health. Sick behavior is the act of the individual in a state of illness to seek healing. The transcultural approach adopted by the client; it is one of the way to success in providing nursing services. It aimed to determine understand the meaning and significance of sick health behavior of the Jambi Malay tribe based on transcultural nursing approach (sunrise model). This research design was a qualitative research. Participants recruited as much as 5 person by purposive sampling method. Data colected with indepth interview and data analyzed by using colaizzi. This study was conducted on July 21st – August 21st 2017 at Muara Kumpeh village. The findings indicated that seven themes by using Sunrise Model theory i.e. 1) religious factors and philosophy of life, 2) social factors and family attachment, 3) factors of cultural values and lifestyle, 4) technological factors, 5) prevailing policy and regulatory factors, 6) economic factors, 7) educational factors. It is expected that it can be input for tribal community of Malay Jambi in order to understand of sick health behaviors in various aspects and able to apply and balance in their culture.Keyword: Sick Health behaviors, Jambi Malay Tribe, Transcultural Nursing